Speaker Identification from Forensic Phonetics: Application of SplitsTree4 Software for Schematic Organization of Linguistic Data - Jimenez Peña, Jhon (2022)
This article presents a proposal for the interpretation and organization of the phonetic characteristics of indubitable and dubitative samples using SplitsTree4 software, with the purpose of clarifying an alleged crime of bribery in the exercise of police functions to the detriment of the State. The dubitted samples were provided by the Public Prosecutor's Office and the indubitable samples were obtained by means of voice sampling; likewise, data anonymity was chosen. First, the relevant phonetic features of the samples were categorized; then, they were assigned a binary value of existence and non-existence; then, the binary information was processed by SplitsTree4 software to regroup the features according to the universe of speakers and show the compatibility between the indicated samples. Finally, the results indicate that the SplitsTree4 software complies with the ordering of phonetic-articulatory data for forensic voice identification.